2012
DOI: 10.1016/j.neuroimage.2012.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity modulates the functional relationship between theory of mind and autobiographical memory

Abstract: Qualitative and quantitative reviews of the neuroimaging literature show that overlapping brain regions support theory of mind (ToM) and autobiographical memory (AM). This overlap has been taken to suggest that individuals draw on past personal experiences to infer others' mental states, but work with amnesic people shows that ToM does not always depend on AM. One variable that may determine the extent to which one relies on AM when inferring another's thoughts and feelings during ToM is whether that individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 58 publications
(119 reference statements)
6
52
0
Order By: Relevance
“…Adult onset hippocampal amnesia patients reported lower levels of trait empathy and demonstrated no increase in prosocial behavior with an empathic mood induction (Beadle et al, 2013). Consistent with recent neuroimaging findings demonstrating that the hippocampus is engaged during theory of mind of personally familiar individuals but not unfamiliar ones (Rabin and Rosenbaum, 2012), a patient with developmental amnesia was specifically impaired in providing a rich description of events related to oneself and close others, but not unfamiliar others (Rabin et al, 2012). Also examining developmental amnesia resulting from perinatal hypoxia, Staniloiu et al (2013) found impairments on complex social judgment and perception tasks.…”
supporting
confidence: 77%
“…Adult onset hippocampal amnesia patients reported lower levels of trait empathy and demonstrated no increase in prosocial behavior with an empathic mood induction (Beadle et al, 2013). Consistent with recent neuroimaging findings demonstrating that the hippocampus is engaged during theory of mind of personally familiar individuals but not unfamiliar ones (Rabin and Rosenbaum, 2012), a patient with developmental amnesia was specifically impaired in providing a rich description of events related to oneself and close others, but not unfamiliar others (Rabin et al, 2012). Also examining developmental amnesia resulting from perinatal hypoxia, Staniloiu et al (2013) found impairments on complex social judgment and perception tasks.…”
supporting
confidence: 77%
“…Finally, further understanding of the mechanisms underlying the interaction between social and mnemonic processes, as when reflecting on the mental states of familiar others (Rabin et al, 2012) or predicting the behavior of social entities (Hassabis et al, 2013), may have important ramifications for social and mnemonic functioning in autism, Alzheimer’s disease, and other clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…This multivariate technique identifies whole brain patterns of activity correlating with experimental design (i.e., tasks, groups) across the length of an event. PLS is a robustly validated (McIntosh et al, 1996 and widely used analysis technique in cognitive neuroscience, including the study of autobiographical memory (e.g., Burianova and Grady, 2007;Rabin and Rosenbaum, 2012;Spreng and Grady, 2010) as well as mood-related changes in neural activity (Keightley et al, 2003). The use of this technique is particularly appropriate in clinical populations (McIntosh and Lobaugh, 2004) because unlike univariate event-related analyses, ST-PLS is not dependent upon assumptions about the shape and time course of the haemodynamic response function, and can thus be used to examine neural differences between patient groups wherever they emerge across the duration of the trial.…”
Section: Fmri: Imaging Datamentioning
confidence: 99%